Media as the Major Factor of the Economic Development in the Era of Globalization - Anabarja, Sarah (Global and Policy Journal of International Relations, 2013)
ABSTRACTThe production and distribution of digital content over electronic communications networks to a wide range of digital devices is experiencing exponential growth. This global media phenomenon has significant ramifications for development but there is insufficient understanding about the dynamics of the process, and uncertainty about many outcomes. Many factors attempted to determine the process of economic development. Political and economical factors are two factors paying the major influence. While not denying the potential importance of these aforementioned factors, this paper contend that the role of media in developing institutions that facilitate economic progress has only recently begun to receive the attention it deserves. Emphasize to the role of media to the development process this paper is discuss the importance of media in overcoming public choice. It is also important to look up for every aspects of media that can influence the government to make their policy and its impact on government transparency and accountability.Keywords: Media, economic development, public choice, government policy.DOI:https://doi.org/10.33005/jgp.v1i02.1995